2016
DOI: 10.24036/02016516483-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan Motivasi Belajar, Mutu Keterampilan Belajar, dan Self Regulated Learning Siswa Kelas Diklat dan Siswa Kelas Reguler

Abstract: This research was conducted as there was a difference between learning achievement of the students in regular class and in training class. Learning motivation, learning skill quality and self regulated learning are factors assumed to affect the students’ learning achievement. This research was intended to: (1) reveal the difference between learning motivation of the students in regular class and in training class, (2) the difference between learning skill quality of the students in regular class and in trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
2
0
3
Order By: Relevance
“…These findings provide recent evidence about the motivation of prospective group members before they follow group guidance. So far, there have been many comparative descriptive and descriptive studies based on gender differences or other aspects that measure student motivation towards learning activities (E.g Edli & Mudjiran, 2015;Hidayat, Nirwana, & Syahniar, 2016) or motivation of students towards certain fields of study or learning activities (E.g, Tasiwan, Nugroho, & Hartono, 2014). Unfortunately, very few research publications have been found about students' motivation to follow group guidance that measures conditions before activities.…”
Section: Discussionmentioning
confidence: 99%
“…These findings provide recent evidence about the motivation of prospective group members before they follow group guidance. So far, there have been many comparative descriptive and descriptive studies based on gender differences or other aspects that measure student motivation towards learning activities (E.g Edli & Mudjiran, 2015;Hidayat, Nirwana, & Syahniar, 2016) or motivation of students towards certain fields of study or learning activities (E.g, Tasiwan, Nugroho, & Hartono, 2014). Unfortunately, very few research publications have been found about students' motivation to follow group guidance that measures conditions before activities.…”
Section: Discussionmentioning
confidence: 99%
“…Secara sederhana, sebuah halaman web dibuat dengan menuliskan perintah-perintah HTML menggunakan perangkat lunak pengolah kata dan menyimpannya dalam format ASCII standar. [8] 2. 6…”
Section: Websiteunclassified
“…Self regulated learning menurut Winne (Santrock, 2008) adalah kemampuan untuk memunculkan dan memonitor sendiri pikiran, perasaan, dan perilaku untuk mencapai suatu tujuan. Senada dengan itu Hidayat, H., Nirwana, H., & Syahniar, S. (2016) menyatakan self regulated learning adalah proses aktif dan konstributif siswa dalam menetapkan tujuan untuk proses belajarnya dan usaha untuk memonitor, mengatur dan mengontrol kognisi, motivasi dan perilaku, yang kemudian semuanya diarahkan dan didorong oleh tujuan dan mengutamakan konteks lingkungan. Selanjutnya Yulianti, P., Sano, A., & Ifdil, I.…”
Section: Introductionunclassified